A framework of negative responses to introversion at work. (15th July 2020) - McCord, Mallory A.; Joseph, Dana L.
Abstract: Despite recent growth in popular press about introversion and negative responses to introversion at work, academic work has yet to directly investigate this topic. This may be at least partly due to a sensitive issue: do negative responses to introversion at work purely constitute mistreatment, or are these legitimate responses to introversion? We propose a framework that incorporates both perspectives as interlinked explanations for this phenomenon: the Stereotype-Driven Process, which is driven by bias and associated with mistreatment, and the Target-Driven Process, which is driven by introversion itself and can be associated with legitimate responses to introversion. As such, this paper describes how negative responses to introversion come about, introduces perceived introversion mistreatment, examines negative outcomes associated with negative responses to introversion, and delineates numerous testable propositions that can guide future research on the topic.